INFLUENCE SOCIO-ECONOMIC SITUATION ON THE EFFECTIVE USE OF MANPOWER AGRICULTURAL ENTERPRISES - Lebid , O.V. (The actual problems of regional economy development, 2016)
In the article, the socio-economic condition of the rural population of Ukraine is a potential basis for the formation of labor farms. Analyzes the quantity of the population of Ukraine. The experience of leading countries for the support of public authorities of the agricultural sector. Analyzes the rural development programs of developed countries and derived from their implementation results. The dependence of the social dimension of economic and determined that it is the main and fundamental, and is a driving force for social development. JEL: Q 00